Improvement of the Ultrasound-Assisted Extraction of Polyphenols from Welsh Onion (Allium fistulosum) Leaves Using Response Surface Methodology - Medina Jaramillo, Carolina (2022)
Welsh onion (Allium fistulosum) leaves contain several bioactive compounds that can be extracted and used to develop new value-added products (e.g., functional foods and dietary supplements). In the current work, optimal ultrasound-assisted extraction (UAE) conditions to obtain extracts with high polyphenols content and DPPH (1,1-diphenyl-2-picrylhydrazil) scavenging activity were identified using response surface methodology. A complete 3k factorial design was used to evaluate the effect of different variables of the UAE (extraction temperature, time, and ethanol concentration) on the polyphenols content and the DPPH scavenging activity of the extracts. The best conditions for UAE to reach both the highest values of total polyphenols content (51.78 mg GAE/100 g) and DPPH scavenging activity (34.07 mg Trolox equivalents/100 g) were an extraction temperature of 60 °C, time of 10 min, and ethanol concentration of 70% v/v. The antioxidant activity of the extracts obtained at the optimal conditions was also evaluated by 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) and ferric reducing antioxidant power (FRAP) assays obtaining values of 155.51 ± 2.80 μM Trolox/100 g and 1300.21 ± 65.55 μM Trolox/100 g, respectively. Moreover, these extracts were characterized by UHPLC-ESI+-Orbitrap-MS analysis finding that cyanidin (6.0 mg/kg) was the phenolic compound found in the highest amount followed by quercetin-3-glucoside (4.4 mg/kg).